2022
DOI: 10.1007/s00247-022-05299-6
|View full text |Cite
|
Sign up to set email alerts
|

Working from home during the COVID-19 pandemic: surveys of the Society for Pediatric Radiology and the Society of Chiefs of Radiology at Children’s Hospitals

Abstract: Background Due to the COVID-19 pandemic, some pediatric radiologists have shifted to working from home; the long-term ramifications for pediatric radiologists and departments have not yet been defined. Objective To characterize experiences of working from home associated with the COVID-19 pandemic and guide expectations after the pandemic is controlled, via separate surveys of Society for Pediatric Radiology (SPR) and Society of Chiefs of Radiology at Children’s Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…Other studies also showed similar results. 10,14,15 However, our data showed a different result. Once the pandemic was under control, activity on the off-site workstations returned to prepandemic levels ( p > 0.05).…”
Section: Discussioncontrasting
confidence: 78%
“…Other studies also showed similar results. 10,14,15 However, our data showed a different result. Once the pandemic was under control, activity on the off-site workstations returned to prepandemic levels ( p > 0.05).…”
Section: Discussioncontrasting
confidence: 78%
“…In contrast to these studies, all our residents were on-site and in the reading room. Our data are supported by subjective evidence from surveys of both radiology faculty and trainees [15,21,23], with a consensus opinion that remote work negatively impacts education. In a survey conducted by Seghers et al, which compared the experiences of radiology faculty working remotely versus on-site, most respondents rated their ability to teach trainees as significantly decreased, with an average rating of 2.7 out of 10 on a scale where 0 represents the maximum diminishment of the work experience when working from home compared to in-hospital [15].…”
Section: Plos Digital Healthsupporting
confidence: 72%
“…Our data are supported by subjective evidence from surveys of both radiology faculty and trainees [15,21,23], with a consensus opinion that remote work negatively impacts education. In a survey conducted by Seghers et al, which compared the experiences of radiology faculty working remotely versus on-site, most respondents rated their ability to teach trainees as significantly decreased, with an average rating of 2.7 out of 10 on a scale where 0 represents the maximum diminishment of the work experience when working from home compared to in-hospital [15]. Similarly, the results of a recent survey by the American Alliance of Academic Chief Residents [21], could be considered a referendum on the efficacy of remote learning: a supermajority (74%) of chief residents reported that remote readouts were significantly less effective when conducted in-person.…”
Section: Plos Digital Healthsupporting
confidence: 72%
See 1 more Smart Citation
“…Radiology services have also seen significant changes in workflow across modalities and a reduction in imaging volumes[ 6 - 8 ]. For example, departments were re-configured to separate COVID-19 patients from non-infected patients, segregation of staff to reduce infection transmission, increased demand for PPE, radiologists reporting from home, and expansion of video conferencing use[ 5 , 9 ]. For patients presenting to the emergency department, general radiography was primarily used due to its accessibility, availability and low radiation levels.…”
Section: Introductionmentioning
confidence: 99%